Cascade energy reemission after inner-shell ionization of atomic gold. Role of photo- and cascade-produced electrons in radiosensitization using gold-containing agents. (July 2023) - Chaynikov, A.P.; Kochur, A.G.; Dudenko, A.I.; Yavna, V.A.
Highlights: Cascade decays of vacancies in K to O shells of the Au atom are simulated. Spectra of cascade-produced electrons and photons are calculated. Most of the absorbed photon energy is re-emitted with electrons and photons. Cascade- and photo-electrons are the principal transmitters of energy to the medium. Abstract: A method of straightforward construction and analysis of the cascade decay trees is applied to calculate photon and electron spectra emitted upon the cascade de-excitation of single inner-shell vacancies in the gold atom produced by photoionization. The energy acquired by the gold atom upon photoionization is split into the following channels: i) energy absorbed by the gold atom itself, ii) energy carried away by the cascade electrons, and iii) energy carried away by the cascade photons. The energies absorbed through channels i–iii are analyzed for the cascade decay of each single vacancy in O to K shells, and presented as functions of incident photon energies based on calculated partial photoionization cross sections. Energy reemitted through channels ii and iii in the cases of O -, N -, M -, L -, and K -ionization make, respectively, 47–60%, 55–69%, 85–89%, 94–96%, and 99% of the initially acquired energy. Cascade-produced electrons and photons eventually transfer their energy to the medium which lays the base for using gold-containing compounds and gold nanoparticles as radiosensitizing agents in radiotherapy. Cascade-produced electrons, as well as photoelectrons, are found to be the principal transmitters of energy to atoms of the environment in the vicinity of the sites of initial ionization. Their relative role in possible radiosensitizing effect is analyzed on the incident photon energy range of 0.01–1000 keV.